Mitogenomes and relatedness do not predict frequency of tool-use by sea otters. (31st March 2017) - Ralls, Katherine; McInerney, Nancy Rotzel; Gagne, Roderick B.; Ernest, Holly B.; Tinker, M. Tim; Fujii, Jessica; Maldonado, Jesus
Abstract : Many ecological aspects of tool-use in sea otters are similar to those in Indo-Pacific bottlenose dolphins. Within an area, most tool-using dolphins share a single mitochondrial haplotype and are more related to each other than to the population as a whole. We asked whether sea otters in California showed similar genetic patterns by sequencing mitogenomes of 43 otters and genotyping 154 otters at 38 microsatellite loci. There were six variable sites in the mitogenome that yielded three haplotypes, one found in only a single individual. The other two haplotypes contained similar percentages (33 and 36%) of frequent tool-users and a variety of diet types. Microsatellite analyses showed that snail specialists, the diet specialist group that most frequently used tools, were no more related to each other than to the population as a whole. The lack of genetic association among tool-using sea otters compared with dolphins may result from the length of time each species has been using tools. Tool-use in dolphins appears to be a relatively recent innovation (less than 200 years) but sea otters have probably been using tools for many thousands or even millions of years.